Challenges of Using AI in Teaching EFL at the University of Duhok (Raparin Journal of Humanities (RJH), 2025)
The potential of integrating Artificial Intelligence (AI) into English as a Foreign Language (EFL) learning is invested in to a significant extent, which yields tangible progress in language teaching, testing, and learning. The use of AI in EFL education, however, is faced with certain challenges and specific barriers. This study aims to investigate the opinions of EFL instructors on these challenges and barriers. This research employs both qualitative and quantitative research strategies, which include interview sessions and a survey questionnaire, with 42 EFL teachers from the departments of English in colleges of Basic Education and Languages at the University of Duhok. The results showed that EFL teachers identify key challenges to AI adoption, including a lack of training, limited institutional support, and unreliable internet connections. Additionally, many teachers express concerns about the costs, the lack of sufficient computers, and the absence of clear guidelines for implementation. These barriers have notably hindered the practical integration of AI in the EFL classroom, limiting teachers' ability to apply new technologies and preventing a full understanding of AI’s potential to support personalized instruction and interactive learning environments. These findings offer valuable insights into methods that help EFL teachers increase their awareness of AI, enabling them to understand how AI can be effectively introduced into EFL practice without fear of failure.